A single asymmetric error-correcting code with 213codewords of dimension 17 - Al-Bassam, S.A. (2000)
A new single asymmetric error-correcting code is proposed. This code is constructed using a product of two codes of smaller dimensions. The proposed code is of dimension 17 and of size 8192, i.e., with 213 codewords. The best known code of dimension 17 has size 7968 and capable of handling 12 information bits only. The only other three known cases of single asymmetric codes accommodating one more extra information bit than the symmetric case are for code dimensions 2, 4, and 16